Modern information methods of study of soils (Journal of Geography and Environmental Management, 2018)
The article presents modern analyses of the baseline data and information that are currently processedby internal relations with homogeneous elements of a structure. Soil information is stored in avisual or electronic form. In the last years was developed the semantic data model of the soils, so theircharacteristics are described by elements of soil structure, which forms the semantics of a single informationspace. Information systems allow to store and process large amounts of soil data. But the article alsodescribes the different research programmes of the soil. Presented by global modeling techniques, andstudies of soil information.A study of the current state of foreign developments in the use of information technology to workwith the soil data showed that the most relevant are soil information system of the third generation, inwhich there are three components: geographic information system enabling work with spatial data; arelational database that provides the functionality of multiple morphological and physico-chemical parametersof soil properties; and use the principles of the Internet, which provides access to the system inreal-time and multiplayer mode.Despite the rapid development of foreign soil information systems, remains an urgent problem ofpreserving the primary sense of the original soil information in the translation of soil information from atext, ≪paper≫ format into electronic form.